(untitled) (Research, Society and Development, 2020)
The study aimed to study corruption in the public sector, seeking to elaborate a concept about the external control of the Public Administration regarding the principles reported in Article 37 of the Federal Constitution. In relation to the collected data, this study is characterized as bibliographic research. It is important to highlight that to combat corruption in Brazil, it is essential to build a new efficient institutional culture, involving various actors of society and the Court of Auditors, in order to preserve public finances.